2020
DOI: 10.1371/journal.pntd.0008902
|View full text |Cite
|
Sign up to set email alerts
|

A scabies outbreak in the North East Region of Ghana: The necessity for prompt intervention

Abstract: Background There is a dearth of data on scabies from Ghana. In September 2019, local health authorities in the East Mamprusi district of northern Ghana received reports of scabies from many parts of the district. Due to on-going reports of more cases, an assessment team visited the communities to assess the effect of the earlier individual treatment on the outbreak. The assessment team furthermore aimed to contribute to the data on scabies burden in Ghana and to demonstrate the use of the International Allianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 41 publications
5
26
1
Order By: Relevance
“…This finding is aligned with the results of studies done previously in Ethiopia, Iraq and Egypt with a prevalence of 2.5%, 3.3%, and 7% respectively [15][16][17]. However, it is lower than studies from Pakistan (38.15%), (47.6%, Nigeria (65.0%), and Ghana (71%) [18][19][20]. The difference in prevalence rates could be attributed to the density of population, might be attributed to family size variation, educational status variation, and might also be related to variation in sociodemographic.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is aligned with the results of studies done previously in Ethiopia, Iraq and Egypt with a prevalence of 2.5%, 3.3%, and 7% respectively [15][16][17]. However, it is lower than studies from Pakistan (38.15%), (47.6%, Nigeria (65.0%), and Ghana (71%) [18][19][20]. The difference in prevalence rates could be attributed to the density of population, might be attributed to family size variation, educational status variation, and might also be related to variation in sociodemographic.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed more than half of scabies diagnosed were moderate in severity which is harmonious with the findings from the Solomon Islands [ 29 ]. However, studies undertaken in Ghana and Liberia among the general population and in northern Ethiopia among school-aged children reported severe scabies among high proportions of study participants [ 17 , 40 , 41 ]. The severity of scabies infestation is directly related to the number of mites found on the skin and the lengthy of time between initial infestation and subsequent diagnosis and treatment [ 20 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, low monthly family income was among the identified factors affecting scabies in children aged 5-14 years. Scabies more commonly affects disadvantaged populations, including PLOS ONE poverty, household crowding, and poor access to healthcare [1,40]. Low-incomes expose families to scabies in two dimensions.…”
Section: Plos Onementioning
confidence: 99%
“…It is common among persons living in poor and overcrowded communities but is also a common condition among patients presenting to hospital with dermatologic conditions in resource poor settings [2,3]. Scabies has also been reported among prisoners, preschool children [4] and within communities of Africa [5][6][7]. The greatest burden of scabies is in low-and middle-income countries where overcrowding and inadequate access to effective treatment serve as drivers of disease transmission.…”
Section: Introductionmentioning
confidence: 99%